To simplify the given expression, we will distribute and combine like terms:
5(0.5k - 1) + 2(0.4 - k)
= 5(0.5k) - 5(1) + 2(0.4) - 2(k)
= 2.5k - 5 + 0.8 - 2k
Combining like terms:
= (2.5k - 2k) + (-5 + 0.8)
= 0.5k - 4.2
So, the simplified expression is 0.5k - 4.2.
Add: 5(0.5k-1)+2(0.4-k). Answer should be in decimal form
7 answers
Subtract 1/2(z+4)-3(1/4z+1). Use fraction in final form
To subtract the given expression, we will distribute and combine like terms:
1/2(z + 4) - 3(1/4z + 1)
= 1/2 * z + 1/2 * 4 - 3 * 1/4 * z - 3 * 1
= 1/2 * z + 2/2 - 3/4 * z - 3
= 1/2 * z + 1 - 3/4 * z - 3
Now, let's find a common denominator for the fractions: 2 and 4 both divide evenly into 4.
= (1/2) * z + (1 - 3/4) * z + (1 - 3)
= (1/2) * z + (4/4 - 3/4) * z + (-2)
= (1/2) * z + (1/4) * z - 2
Combining like terms:
= (1/2 + 1/4) * z - 2
= (2/4 + 1/4) * z - 2
= (3/4) * z - 2
So, the simplified expression is (3/4)z - 2.
1/2(z + 4) - 3(1/4z + 1)
= 1/2 * z + 1/2 * 4 - 3 * 1/4 * z - 3 * 1
= 1/2 * z + 2/2 - 3/4 * z - 3
= 1/2 * z + 1 - 3/4 * z - 3
Now, let's find a common denominator for the fractions: 2 and 4 both divide evenly into 4.
= (1/2) * z + (1 - 3/4) * z + (1 - 3)
= (1/2) * z + (4/4 - 3/4) * z + (-2)
= (1/2) * z + (1/4) * z - 2
Combining like terms:
= (1/2 + 1/4) * z - 2
= (2/4 + 1/4) * z - 2
= (3/4) * z - 2
So, the simplified expression is (3/4)z - 2.
Subtract (3b-2c)-(6c+2b)-(b+c)
To perform the subtraction, we will remove the parentheses and then combine like terms:
(3b - 2c) - (6c + 2b) - (b + c)
= 3b - 2c - 6c - 2b - b - c
= (3b - 2b - b) + (-2c - 6c - c)
= 0b - 9c
Simplifying this expression, we get:
= 0 - 9c
= -9c
Therefore, the simplified form of the expression (3b - 2c) - (6c + 2b) - (b + c) is -9c.
(3b - 2c) - (6c + 2b) - (b + c)
= 3b - 2c - 6c - 2b - b - c
= (3b - 2b - b) + (-2c - 6c - c)
= 0b - 9c
Simplifying this expression, we get:
= 0 - 9c
= -9c
Therefore, the simplified form of the expression (3b - 2c) - (6c + 2b) - (b + c) is -9c.
What is the Expression 4+8(3x-2) -7x when simplified? Apply the order of operations and the commutative and distributive properties. Show all your work
To simplify the expression 4 + 8(3x - 2) - 7x, we will apply the order of operations and the commutative and distributive properties.
First, we will simplify the expression within the parentheses:
8(3x - 2)
= 24x - 16
Now, let's substitute this simplified expression back into the original expression:
4 + 24x - 16 - 7x
Next, we will combine like terms:
(24x - 7x) + (4 - 16)
= 17x - 12
Therefore, the simplified form of the expression 4 + 8(3x - 2) - 7x is 17x - 12.
First, we will simplify the expression within the parentheses:
8(3x - 2)
= 24x - 16
Now, let's substitute this simplified expression back into the original expression:
4 + 24x - 16 - 7x
Next, we will combine like terms:
(24x - 7x) + (4 - 16)
= 17x - 12
Therefore, the simplified form of the expression 4 + 8(3x - 2) - 7x is 17x - 12.